Illness perceptions as predictors of psychological distress among head and neck cancer survivors: a longitudinal study. Issue 11 (11th October 2018) - Zhang, Na; Fielding, Richard; Soong, Inda; Chan, Karen KK; Lee, Conrad; Ng, Alice; Sze, Wing Kin; Tsang, Janice; Lee, Victor; Lam, Wendy Wing Tak
Abstract: Background: Leventhal's commonsense model implies illness perceptions influence illness outcomes. This study examined illness perceptions among head and neck cancer survivors, and whether these predicted subsequent psychological distress. Methods: A total of 124 survivors of head and neck cancer (87% nasopharyngeal carcinoma; NPC) completed measures of psychological distress (Hospital Anxiety and Depression Scale; HADS), illness perceptions (Brief Illness Perception Questionnaire; B‐IPQ), dispositional optimism (revised Chinese version of the Life Orientation Test; C‐LOT‐R), and clinical and demographic data approximately12.9 months after diagnosis (T1). Six months later (T2) psychological distress (HADS) was again measured. Adjusted multivariate analyses tested whether illness perceptions predicted T2 HADS scores. Results: Illness perception dimensions were significantly intercorrelated (0.01‐0.68), explaining 8.0% of anxiety and 4.8% of depression symptom variability at T2. After adjustment for T1 distress, illness identity ( β = 0.270, P < .01) and sex identification as a woman ( β = 0.275, P < .01) predicted T2 anxiety symptoms while illness identity ( β = 0.195, P < .05), unemployment ( β = 0.195, P < .05), and pessimism ( β = –0.227, P < .01) predicted T2 depression symptoms. Conclusion: Perceived illness identity predicted psychological distress, accounting for modest levels of distress variance. Unresolved symptoms may exacerbate distress.